ANALISIS WACANA KRITIS BERITA “OJOL MATIKAN APLIKASI” DALAM PERSPEKTIF MODEL TEUN A. VAN DIJK - Alien Kurnia Warya Selia; Hari Bakti Mardikantoro; Rustono (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to analyze the textual dimensions of a news article titled “Ojol Drivers Shut Down Apps; Beware of Traffic Jams in Jakarta During Today’s Protest,” published by CNN Indonesia, using Teun A. van Dijk’s critical discourse analysis model. This study employs a descriptive qualitative approach using a documentary method to analyze the online news text. The analysis focuses on three main structures: macrostructure, superstructure, and microstructure. The results show that at the macro level, the news theme centers on a large-scale demonstration by online motorcycle taxi drivers as a form of protest against government policies and digital transportation apps. At the superstructure level, the news framing highlights social impacts such as traffic congestion and transportation disruptions as the primary focus, while substantive demands are placed at the end. At the microstructure level, the use of active sentences emphasizes the role of online motorcycle taxi drivers as social actors, whereas passive sentences tend to neutralize the role of authorities. Lexical choices such as “shutting down the app” function metaphorically as a symbol of digital resistance. Additionally, rhetorical elements such as bold and italicized text reinforce ideological emphasis. These findings confirm that media language plays a role in shaping public perception, thus the need to develop critical awareness of discourse structures in language education and media literacy.